Carcinoma Cuniculatum of the Foot Invading the Bone Mimicking a Pseudo-Epitheliomatous Reaction to an Acute Osteomyelitis. Issue 1 (March 2016) - Arisi, Mariachiara; Zane, Cristina; Edu, Irina; Battocchio, Simonetta; Petrilli, Giulia; Calzavara-Pinton, Pier
Abstract Carcinoma cuniculatum is a rare variant of squamous cell carcinoma. The clinical presentation is usually a non-verrucous exophytic plaque or tumor of the plantar region with a penetration in the deep tissues. Histological examination shows a proliferation of well-differentiated keratinocytes. We describe a patient affected by a slowly enlarging tumoral lesion overlying the fifth metatarsum of the left foot. Clinical examination and radiological investigations suggested a chronic osteomyelitis and a first histological examination of a punch biopsy was suggestive of a pseudo-epitheliomatous hyperplasia. The patient underwent several cycles with systemic antibiotics without improvement. Finally, the fifth metatarso was amputated and the skin lesion was completely removed. The histological examination of the whole operatory mass allowed a diagnosis of carcinoma cuniculatum invading the bone.